Sebaran Mikroba Tanah pada Berbagai Jenis Penggunaan Lahan Di Kawasan Bandung Utara - Muhammad Amir Solihin; Betty Natalie Fitriatin (Soilrens, 2017)
North of Bandung have regional multifunction. Thereby, land resources management based on existing land characteristic is important. One of important land biophysic potential is soil microorganism. Study location area is 14.492 Hectare. The research methode is survey research which characterization analysis using remote sensing interpretation, geographical information system analysis, and soil microorganism population analysis. Research result shows variation of biodiversity potency of several soil microorganism type in study location. High potency of soil microorganism in 5.020,23 Hectare (34,64%) areas, medium potency in 2.309,86 Hectare (15,94%) areas and low potency in 2.362,76 Hectare (16,30%) areas. Those biophysic potency important to sustainable agriculture development based on organic farming in the North of Bandung Area.Keywords: humic acid, role of humic acid